1997
DOI: 10.1192/bjp.171.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia and depression among elderly people in Black and ethnic minorities

Abstract: A complete enumeration of the elderly in ethnic minority groups is best achieved by using several different methods. Diagnosis of dementia may be misleading among those who do not speak the dominant language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
3
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 11 publications
5
73
3
5
Order By: Relevance
“…Diversas investigações epidemiológicas demonstraram que a depressão é o distúrbio da saúde mental mais freqüente na terceira idade 12,13,7,14 , além de ser um dos que mais gastos econômicos gera com a saúde. 15 O atendimento emergencial de idosos deve, também, considerar que a depressão está associada à maior morbidade e mortalidade nessa faixa etária, particularmente quando doença física ou declínio cognitivo estão presentes.…”
Section: Método E Análise Dos Dadosunclassified
“…Diversas investigações epidemiológicas demonstraram que a depressão é o distúrbio da saúde mental mais freqüente na terceira idade 12,13,7,14 , além de ser um dos que mais gastos econômicos gera com a saúde. 15 O atendimento emergencial de idosos deve, também, considerar que a depressão está associada à maior morbidade e mortalidade nessa faixa etária, particularmente quando doença física ou declínio cognitivo estão presentes.…”
Section: Método E Análise Dos Dadosunclassified
“…A few community surveys have been carried out, and they have found rates of anxiety, depression and dementia to be at least comparable with those in the indigenous elderly population. For example, a recent survey of the elderly ethnic minority communities in Liverpool (McCracken et al, 1997) found rates of depression that were slightly higher than in the indigenous population. The nonEnglish speaking ethnic minorities had higher rates of dementia than those minorities that spoke English, who had rates similar to those in the indigenous population.…”
Section: Epidemiologymentioning
confidence: 99%
“…Though the MMSE is validated in Gujarati, there are little data on its use in Punjabi. Whilst the proportion of Black and Minority Ethnic people affected by dementia in the UK is broadly similar to that found among white people (Shah, 2010), higher levels have been found in non-English-speaking groups (McCracken, 1997). Importantly, there have been no large-scale UK prevalence studies to indicate that our findings may reflect a general population difference in cognitive impairment.…”
Section: Discussionmentioning
confidence: 49%